Local communities and sport activities expenditures and image: residents’ role in sustainable tourism and recreation - Perna, Fernando (2020)
The practice of sports by resident communities is a tool for healthy lifestyles, inclusive growth and the promotion of sustainable cities. Nevertheless, the relationship between sport, tourism and recreation still remain an under researched theme. Focusing on the economic pillar of sustainability, this study intends to quantify and analyse the economic costs incurred by families in formal and informal sport practices, as well as the contribution of these activities and related events to the territory's image projection and attractiveness, by overlapping resident's and visitor's perception of sports in the destination. Applied to the municipality of Guimaraes (Portugal), this analysis of the sports consumer's behaviour contributes to filling the gap of knowledge resulting from the studies that, as a rule, exclusively evaluate the investments (supply) and/or the expenses (demand) of events and not the regular practice of sport. A total of 179 questionnaires were applied to residents throughout 2017, through the self-administrate questionnaire method. Findings reveal that residents see sports as one of the factors contributing to the identity of the municipality, underlying motivations for participation as the search for happiness, health, wellbeing, and fun. Expenditures generate multiplier effects in the local economy, allowing to compare growth scenarios. This analysis is a scientific instrument to support territorial innovation and the decision at the local level of public policies for sustainable development, in agreement with objective eight of sustainability defined by the United Nations.